2018
DOI: 10.4103/ajns.ajns_336_16
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of decision tree to predict survival in patients with glioblastoma multiforme with the use of clinical and imaging features

Abstract: Background: Machine learning is a type of artificial intelligence which aims to improve machine with the ability of extracting knowledge from the environment. Glioblastoma multiforme (GBM) is one of the most common and aggressive primary malignant brain tumors in adults. Due to a low rate of survival in patients with these tumors, machine learning can help physicians for better decision-making. The aim of this paper is to develop a machine learning model for predicting the survival rate of patients with GBM ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Emblem et al [ 15 ] used a SVM and a whole- tumor cerebral blood volume for this purpose, while Nematollahi et al [ 40 ] proposed the C5.0 decision tree model, with tumor width and Karnofsky performance status scores being the most critical parameters for prediction of survival.…”
Section: Resultsmentioning
confidence: 99%
“…Emblem et al [ 15 ] used a SVM and a whole- tumor cerebral blood volume for this purpose, while Nematollahi et al [ 40 ] proposed the C5.0 decision tree model, with tumor width and Karnofsky performance status scores being the most critical parameters for prediction of survival.…”
Section: Resultsmentioning
confidence: 99%
“…This study was based on the hypothesis that connectomics-based features could capture tumor-induced network level alterations that can influence prognosis, underlining the importance of including rs-fMRI in the pre-surgical workout of patients with glioma. Nematollahi et al [ 71 ] showed the impact of a decision tree trained using both clinical and radiomic features. They obtained an accuracy of 90.9% for OS classification, using the C5.0 decision tree algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…For the SC task, Single Layer Neural Network [ 93 ], SVM [ 64 ], Decision Trees [ 71 ], and 3D-CNN plus a SVM [ 75 ] achieved the highest accuracy (>90.7%). Characteristics and performance of those four methods are summarised in Table 2 , a graphical representation of the accuracy of the best four methods is displayed in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations